Faktor Yang Mempengaruhi Kebijakan Deviden - Radina Modjaningrat (STIE Jambatan Bulan, 2021)
The purpose of this research is for dividend policy decision making there is a conflict between interested parties in accordance with the agency theory, namely between shareholders and management. Empirical studies have been conducted to examine factors that affect dividend policies conducted by companies but the results showed different results. In the opinion of the authors the most influential factors on dividend policy are profitability, leverage, liquidity, institutional ownership and political connections. Empirical studies on the influence of profitability, leverage, liquidity, institutional ownership and political connections are conducted simultaneously on dividend policies. This is done to prove that these factors if tested simultaneously, whether to influence the dividend policy moreover there is a political connection in it, especially research on the influence of political connections to dividend policy in Indonesia is still very rare